Therapeutic activity of an interleukin‐4/interleukin‐13 dual antagonist on oxazolone‐induced colitis in mice. Issue 3 (November 2014) - Kasaian, Marion T.; Page, Karen M.; Fish, Susan; Brennan, Agnes; Cook, Timothy A.; Moreira, Karen; Zhang, Melvin; Jesson, Michael; Marquette, Kimberly; Agostinelli, Rita; Lee, Julie; Williams, Cara M. M.; et al.
Summary Interleukin‐4 (IL‐4) and IL‐13 are critical drivers of immune activation and inflammation in ulcerative colitis, asthma and other diseases. Because these cytokines may have redundant function, dual targeting holds promise for achieving greater efficacy. We have recently described a bifunctional therapeutic targeting IL‐4 and IL‐13 developed on a novel protein scaffold, generated by combining specific binding domains in an optimal configuration using appropriate linker regions. In the current study, the bifunctional IL‐4/IL‐13 antagonist was evaluated in the murine oxazolone‐induced colitis model, which produces disease with features of ulcerative colitis. The bifunctional IL‐4/IL‐13 antagonist reduced body weight loss throughout the 7‐day course of the model, and ameliorated the increased colon weight and decreased colon length that accompany disease. Colon tissue gene expression was modulated in accordance with the treatment effect. Concentrations of serum amyloid P were elevated in proportion to disease severity, making it an effective biomarker. Serum concentrations of the bifunctional IL‐4/IL‐13 antagonist were inversely proportional to disease severity, colon tissue expression of pro‐inflammatory genes, and serum amyloid P concentration. Taken together, these results define a panel of biomarkers signifying engagement of the IL‐4/IL‐13 pathway, confirm the T helper type 2 nature of disease in this model, and demonstrate the effectiveness of dual cytokine blockade.